Source Apportionment of Elemental Carbon in Different Seasons in Hebei, China - Hou, Dongli; Zhang, Xiang; Zhao, Jiangwei; Qiang, Jie; Wang, Jianguo; Wang, Peng; An, Qingxian; Wang, Yang; Wang, Liwei; Yuan, Shihui; Zhang, Feng (Frontiers in Environmental Science, 2022)
Black carbon (BC), also termed as elemental carbon (EC) is a strong light absorbing substance. It can disturb the radiation balance between earth and atmosphere resulting in changing regional and global climate conditions. This study conducted a thorough analysis of EC in Hebei during different seasons and provided comprehensive EC emission data in the Beijing-Tianjin-Hebei (BTH) region for future policy making connected with air pollution mitigation and control. The results showed that the concentration of EC during the sampling period varied from 0.01 to 18.4 μg/m3 with a mean value of 2.6 ± 2.8 μg/m3. The EC source apportionment exercise identified four regular emission sources for all seasons, including traffic-related emissions, coal combustion, biomass burning and mineral dust. Annually, traffic-related emissions were the primary EC contributor with an annual average contribution of 38%, followed by biomass burning (30%) and coal combustion (25%). In addition, the EC mass concentration at Shijiazhuang was also influenced by diverse pollutants from upwind regions. This study shows that traffic emissions are a major contributor to EC mass concentration in Shangjiazhuang and highlights that regional joint control of air pollution is important to local air quality.